The effect of macroeconomic variable towards purchasing power parity: Evidence of Japan / Nur Syaza Syahirah Johari - Johari, Nur Syaza Syahirah (Faculty of Business and Management, 2018)
Purchasing power parity implies that a person should be able to buy the same goods in different country with the same amount of common currency, once it is converted. Generally purchasing power parity closely involves with a foreign exchange rate of the country and the national price level for that foreign country. The purpose of this research is to examine the impact of macroeconomic variable towards purchasing power parity. The macroeconomic variables include gross domestic product, real exchange rate and inflation rate. There are numerous findings found that there is positive relationship between gross domestic product and inflation rate with purchasing power parity. However, some papers found a negative relationship between real exchange rate and purchasing power parity. Thus, this topic is heatedly debated across time, does macroeconomic variable affect purchasing power parity? This research was carried out to examine the impact of macroeconomic variables towards purchasing power parity in Japan. This research was done for period of 1980 to 2016, by extracting the data from World Bank data with a total observation of 37 years. The independent variable to measure purchasing power parity include gross domestic product, real exchange rate and inflation rate. The collected data was analyzed using descriptive means, correlation analysis and multiple linear regressions via E-Views. Ordinary Least Squares (OLS) method was used in this research to examine the relationship between macroeconomic variables and purchasing power parity.